Theoretical Issues in Nigeria's Democracy and National Security - Adesina, Julius (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026, 2026)
Nigeria's democratic journey has been marked by numerous challenges, raising concerns about the efficacy of its democratic system in ensuring national security. This paper examines the theoretical issues underlying Nigeria's democracy and national security, highlighting the complexities and contradictions that have hindered the country's progress. The liberal democratic theory, which emphasizes individual rights, free markets, and good governance, has been the dominant framework guiding Nigeria's democratic experiment. However, this theory has limitations in addressing Nigeria's security challenges, particularly in the context of deep-seated ethnic and regional divisions. The securitization theory, which posits that security is a socially constructed concept, offers valuable insights into Nigeria's security landscape. The paper explores how various groups and interests have securitized issues like terrorism, kidnapping, and communal conflicts, often to the detriment of human security and democratic governance. Furthermore, the paper analyzes the impact of ethnic and regional politics, corruption, and weak institutions on Nigeria's democratic consolidation and national security. These factors have undermined the state's capacity to provide security and deliver public goods, creating an environment conducive to insecurity and instability. The paper concludes that Nigeria's democracy and national security are intertwined, and that addressing the theoretical issues underlying these concepts is crucial for ensuring the country's stability and prosperity. It argues that a more nuanced understanding of the complex relationships between democracy, security, and development is necessary to overcome the challenges facing Nigeria and to build a more secure and democratic polity. Keywords: Democracy, Liberal Theory, Securitization, Regional Politics and Corruption.